A Comparison Study on the Magneto-Responsive Properties and Swelling Behaviors of a Polyacrylamide-Based Hydrogel Incorporating with Magnetic Particles - Chanchan Xu (MDPI AG, 2021)
This work investigates the mechanical properties, microstructures, and water-swelling behavior of a novel hydrogel filled with magnetic particles. The nanoparticles of magnetite (Fe3O4) and the micro-particles of carbonyl iron (CI) were selected and filled into a polyacrylamide (PAAM) hydrogel matrix to create two types of magnetic hydrogels. The isotropy and anisotropy of magnetic hydrogels are also presented in this study. The isotropic samples were cured without applying a magnetic field (MF), and the anisotropic samples were cured by applying an MF in the direction perpendicular to the thickness of the samples. The effects of the size, content, and inner structures of magnetic particles on the magneto-responsive and swelling properties of magnetic hydrogels were investigated. It was found that the magnetorheological (MR) effect of anisotropic samples was apparently higher than that of isotropic samples, and the hydrogels with CI exhibited a noticeable MR effect than those with Fe3O4. The storage modulus can be enhanced by increasing the filler content and size, forming an anisotropic structure, and applying an external MF. In addition, the magnetic hydrogels also have a swelling ability that can be tuned by varying the content and size of the particle fillers.